Dislodged biliary stent causes lower gastrointestinal hemorrhage four years postendoscopic retrograde cholangiopancreatography. Issue 7 (15th May 2018) - Papanikolaou, Ioannis S.; Tziatzios, Georgios; Gkolfakis, Paraskevas; Parasyris, Stavros; Kizgala, Polyxeni; Economopoulos, Nikolaos; Papadopoulos, Iordanis N.; Dimitriadis, George D.; Triantafyllou, Konstantinos
Key Clinical Message: Endoscopic biliary stent placement is an efficient method for the decompression of the biliary system in various benign and malignant causes. Dislocation and stent migration is a well‐known complication, with most displaced stents passing through the bowel, uneventfully. Rarely, migrated stents can be accounted for potentially life‐threatening complications. Abstract : Endoscopic biliary stent placement is an efficient method for the decompression of the biliary system in various benign and malignant causes. Dislocation and stent migration is a well‐known complication, with most displaced stents passing through the bowel, uneventfully. Rarely, migrated stents can be accounted for potentially life‐threatening complications.